Hubungan pola belanja online dengan kuantitas sampah pada mahasiswa Fakultas Kesehatan Masyarakat - Syahputra, Adi Kurniawan; Indirawati, Sri Malem (Talenta Publisher, 2025)
Waste remains a national issue. The waste generated in Medan City amounted to 628.7 thousand tons per year in 2022, sourced primarily from household waste. The phenomenon of online shopping among students contributes to the generation of waste in the form of plastic and cardboard. This study aims to analyze the relationship between online shopping patterns and waste quantity among students of the Faculty of Public Health. This research is an analytical survey with a cross-sectional study design. The study was conducted at the University of North Sumatra. The population comprised 361 students from the Faculty of Public Health, Class of 2022, with a sample size of 78 students determined using the Slovin formula. Data was collected through observation, direct interviews using questionnaires, and measurement of waste quantity using a digital scale. The data analysis method was conducted in two stages: univariate analysis using frequency and bivariate analysis using the chi-square test with a significance level of α = 5% (0.05). The results showed a significant relationship between online shopping patterns based on online shopping expenses (p = 0.001) and shopping frequency (p = 0.001). However, there was no significant relationship between online shopping patterns based on types of shopping (p = 0.091), students' knowledge (p = 0.450), and students' attitudes (p = 1.000) toward waste quantity. The study suggests that parents and students should pay more attention to online shopping patterns and waste management as an effort to reduce waste.